Forecasting tourism arrival in Panama using ARIMA models - Cubilla-Montilla, Mitzi; Frende Vega, María de los Ángeles; Cruz, Clara Elena; Muñoz Agrazal, Arnold O. (Revista de Ciencias Sociales, 2025)
The tourism industry stands out as a significant source of revenue. Beyond driving economic growth and job creation, tourism also plays a key role in stimulating infrastructures development and promoting services tourist. This study aimed to forecast tourist arrivals in Panama using ARIMA models. Monthly data on tourist arrivals to Panama were collected. The results show that the ARIMA model provides reasonable and useful forecasts for tourist arrivals in Panama, with an acceptable level of accuracy. Therefore, in conclusion, the results of this study become significant for the strategic planning of tourism in Panama, in response to the dynamics of this important sector of the national economy.